Chiral Cationic Chromophores: A New Class of Efficient Ultrabroadband Organic THz Crystals - Yang, Jeong A.; Lee, Chae Won; Kim, Chaeyoon; Auer, Michael; Yu, In Cheol; Jungkwon, O. H.; Yoon, Woojin; Yun, Hoseop; Kim, Dongwook; Jazbinsek, Mojca; Rotermund, Fabian; Kwon, O. Pil (Advanced Optical Materials, 2024)
A strategic approach to develop efficient ultra-broadband terahertz (THz) crystals involves the incorporation of different electron donating groups (EDGs) into cationic chromophores. In contrast to the widely utilized non-cyclic 4-(dimethylamino)phenyl (DA) EDG, cyclic 5-membered 4-(2-(hydroxymethyl)pyrrolidine-1-yl)phenyl (PB) and cyclic 6-membered 4-(3-(hydroxymethyl)piperidin-1-yl)phenyl (PN) EDGs exhibit an asymmetrical shape with a strongly interacting hydroxymethyl group at the chiral center. Notably, the PB EDG shows narrower intrinsic vibrational states with lower conformational flexibility and smaller ring flips compared to the PN EDG. In the crystalline state, introducing the PB EDG leads to the formation of a new class of nonlinear optical assembly, the so-called stair-type cation-anion assembly. This assembly demonstrates optimal chromophore alignment with state-of-the-art effective first hyperpolarizability (209 × 10−30 esu). Furthermore, the PB EDG-based crystals exhibit significantly lower THz absorption compared to previously reported benchmark crystals. In THz wave generation experiments, PB EDG-based crystals demonstrate state-of-the-art efficiency and ultrabroad spectral bandwidth, featuring a cut-off frequency of up to 16 THz.
Keywords: Broadband terahertz; Cationics; Electron-donating group; Group-based; Organic crystal; Organics; State of the art; Strategic approaches; Tera Hertz; Ultra-broadband; nonlinear optics; organic crystals; terahertz waves